Strategies to Overcome Challenges and Seize Opportunities for Born Global SMEs: A Systematic Literature Review - Ade Ria Nirmala; Badri Munir Sukoco; Dian Ekowati; Fiona Niska Dinda Nadia; Yakuttinah Marjan; Uswatun Hasanah (SAGE Open)
Born Global small and medium enterprises (SMEs) must survive, grow, and develop on the international market. Therefore, the appropriate strategy is needed to overcome challenges and seize opportunities. This paper presents an up-to-date review of this subject, using the Systematic Literature Review (SLR) method with PRISMA diagrams to analyze papers published under the theme of Born Global SMEs on both the Web of Science (WoS) and Scopus, totaling 549 and 1,365 papers, respectively. Approximately 1,914 papers were extracted from these databases, of which 57 met the review selection criteria, thus included in the review. The review found that SME strategies generally emphasize adaption, strengthening innovation, and technology to deal with the global market. In addition, one of the key findings in this review is that founders and leaders are key in the internationalization of SMEs into Born Global. Born Global SMEs are grounded in and take advantage of the international experiences of their founders or leaders to form global networks in overcoming limited resources and reach market niches as the main strategies in addition to adaptive, innovation, and technology strategies. The question of what internationalization framework is most appropriate for describing and predicting the growth, development, and even survival of Born Global SMEs has not been comprehensively studied. This study offers to learn the strategy of Born Global SMEs in the rationalization to face challenges or obstacles and seize opportunities that are essential.